2011
DOI: 10.4168/aair.2011.3.4.251
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum 25 Hydroxy Vitamin D Levels and Asthma in Children

Abstract: PurposeAsthma and other allergic disorders have increased over the past decades in nearly all nations. Many studies have suggested the role of vitamin D deficiency in both T-helper1 and T-helper2 diseases; however, the association between vitamin D, allergy, and asthma remains uncertain. In this study, the associations of 25-hydroxy vitamin D3 levels with asthma and with the severity of asthma were evaluated.MethodsThis cross-sectional study was conducted on 50 asthmatic children and 50 healthy controls aged 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
102
3
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 28 publications
17
102
3
9
Order By: Relevance
“…A similar case control study involving 50 asthmatic children and 50 controls found a significant difference in 25(OH)D levels and also a significant inverse correlation with asthma severity (15) . However, another study (20) , powered to detect an 18 % difference in total 25(OH)D levels failed to detect either a significant difference in 25(OH)D levels or a correlation with asthma severity in a similar case-control study in 80 asthmatic adults and 80 controls.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A similar case control study involving 50 asthmatic children and 50 controls found a significant difference in 25(OH)D levels and also a significant inverse correlation with asthma severity (15) . However, another study (20) , powered to detect an 18 % difference in total 25(OH)D levels failed to detect either a significant difference in 25(OH)D levels or a correlation with asthma severity in a similar case-control study in 80 asthmatic adults and 80 controls.…”
Section: Discussionmentioning
confidence: 73%
“…Another study from northern Italy showed a direct correlation between asthma control and serum 25(OH)D in a cohort of asthmatic children (14) . Other cross-sectional studies in children have shown that serum 25(OH)D concentrations are directly correlated with pulmonary function parameters, such as forced expiratory volume in one second (15) , and also inversely correlated with asthma severity and airway smooth muscle mass (16) .…”
Section: Introductionmentioning
confidence: 95%
“…D vitamininin aynı zamanda astım şiddeti ve düşük steroid yanıtıyla ilişkili olan Th17 sitokinlerin üretimini de inhibe ettiği gösterilmiştir. D vitamini ayrıca steroid dirençli astımda glukokortikoide olan yanıtı ters çevirebilir (6,9,31). D vitamini eksikliğinin kortikosteroidlere yanıtın azalmasına neden olması astım ataklarına katkıda bulunabilir.…”
Section: Astımlı çOcuklar Ve Kontrol Grubunun Laboratuvar Sonuçlarıunclassified
“…We included studies with data on the study group of asthma and COPD and in a control group of non-asthmatics and non-COPD: 7 studies were in children (Brehm et al, 2010;Freishtat et al, 2010;Rothers et al, 2011;Alyasin et al, 2011;Bener et al, 2012;Brehm et al, 2012;Goleva et al, 2012); 3 studies were with adults (Li et al, 2011;Persson et al, 2012;Zhou et al, 2012); 2 studies were on COPD (Persson et al, 2012;Zhou et al, 2012), and 8 studies on asthma. Studies without a control group were excluded.…”
Section: Studies and Interventions And Inclusion And Exclusion Criteriamentioning
confidence: 99%